2020
DOI: 10.1371/journal.pntd.0008949
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic risk of arboviral diseases: Determining the habitats, spatial-temporal distribution, and abundance of immature Aedes aegypti in the Urban and Rural areas of Zanzibar, Tanzania

Abstract: Background In Zanzibar, little is known about the arboviral disease vector Aedes aegypti in terms of abundance, spatio-temporal distribution of its larval habitats or factors associated with its proliferation. Effective control of the vector requires knowledge on ecology and habitat characteristics and is currently the only available option for reducing the risk of arboviral epidemics in the island nation of Zanzibar. Methodology We conducted entomological surveys in households and surrounding compounds from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
2
11
1
2
Order By: Relevance
“…A great number of studies have reported strong associations between the abundance of Aedes mosquitoes and their larval habitats and poorly managed disposables as well as decorative containers [ 49 51 ]. These materials can hold water and organic debris for long periods, providing relatively stable micro-environmental and microclimatic conditions for proliferation of diverse mosquito species [ 24 , 25 , 51 , 52 ]. We also found high productivity of Aedes mosquitoes, particularly Ae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A great number of studies have reported strong associations between the abundance of Aedes mosquitoes and their larval habitats and poorly managed disposables as well as decorative containers [ 49 51 ]. These materials can hold water and organic debris for long periods, providing relatively stable micro-environmental and microclimatic conditions for proliferation of diverse mosquito species [ 24 , 25 , 51 , 52 ]. We also found high productivity of Aedes mosquitoes, particularly Ae.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti and Ae. bromeliae across urban and rural areas of Zanzibar Island (also known as Unguja) has also been recently confirmed [ 23 25 ]. Infestation of Zanzibar Archipelago by these vectors is a serious threat, as arboviral epidemics will have devastating impacts on the fragile public health system and the tourism-based economy.…”
Section: Introductionmentioning
confidence: 96%
“…Urban-adapted Ae. aegypti larvae are known to develop within open containers including cemetery headstones, plant pots, rain barrels, abandoned tires, and bromeliads, which tend to accumulate nutrients and organic matter (17,(52)(53)(54). Outdoor and laboratory water sources were used in this study (Supplemental Table 1).…”
Section: Mosquito Rearingmentioning
confidence: 99%
“…These findings suggest that circulation of DENVs on the Zanzibar islands is under-recognized, as most likely for other arboviruses. Notably, we recently identified widespread infestation of urban and rural communities on Unguja Island by Aedes aegypti , the main vector of dengue, chikungunya, yellow fever and Zika viruses [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…While available findings [ 27 , 28 ] suggest an overt risk of epidemic spread of MBVDs throughout all communities of the archipelago, this risk is projected to remain high through 2050 in the coastal regions of Tanzania including Zanzibar due to expanding presence of infected Aedes aegypti [ 29 ]. As evidenced by the 2005–2006 chikungunya outbreak on La Reunion, large-scale MBVD epidemics can have devastating social and economic consequences to small-island communities such as Zanzibar that are heavily dependent on global tourism [ 30 ].…”
Section: Introductionmentioning
confidence: 99%